Efficacy of erenumab in chronic migraine patients with and without ictal allodynia. (October 2021) - Lipton, Richard B; Burstein, Rami; Buse, Dawn C; Dodick, David W; Koukakis, Reija; Klatt, Jan; Cheng, Sunfa; Chou, Denise E
Background: Ictal cutaneous allodynia, common in chronic migraine, is associated with reduced responses to acute treatment with triptans. Allodynia's impact on the efficacy of newer preventive treatments such as erenumab is unknown. Methods: Post-hoc subgroup analysis of a double-blind, randomized, placebo-controlled 12-week study of erenumab in chronic migraine, contrasting those with no allodynia with those with moderate-severe allodynia assessed with the Allodynia Symptom Checklist-12, was undertaken. Results: Of 648 randomized individuals with baseline Allodynia Symptom Checklist-12 scores, 386 (59.6%) had no allodynia and 153 (23.6%) had moderate-to-severe allodynia. Mean (standard deviation) baseline monthly migraine days were 17.6 (4.8) and 18.9 (4.3), respectively. Compared to placebo, the erenumab group had greater reductions in monthly migraine days and monthly acute migraine-specific medication days in both no allodynia and allodynia subgroups. Mean (95% confidence interval) treatment differences in change from baseline for monthly migraine days at week 12 were −2.5 (−3.7, −1.4) in the no allodynia subgroup and −3.3 (−5.3, −1.3) in the moderate-severe allodynia subgroup. Change in acute migraine-specific medication days were −3.3 (−4.3, −2.3) and −2.5 (−4.3, −0.8), respectively. Conclusions: Erenumab's efficacy in reducing monthly migraine days and acute migraine-specific medication days in chronic migraine was not impacted by the presence of moderate-severe ictal allodynia. Trial registration: ClinicalTrials.gov NCT02066415